Peran Guru Dalam Membentuk Karakter Siswa di SMA Syekh Abdul Qodir Al-Jailani Rangkang Kraksaan Probolinggo - Siti Munawaroh; Ahmad Fauzi; Herwati Herwati (LP3M IAI Al Urwatul Wutsqo Jombang, 2025)
This study aims to analyse in depth the role of Islamic Religious Education (PAI) teachers in the character building of students at SMA Sheikh Abdul Qodir Al-Jailani Rangkang, Kraksaan, Probolinggo. This study focuses on the formation of the character of faith, fear of God Almighty, and noble character in the context of pesantren-based schools. The research approach used is descriptive qualitative, with data collection techniques through participatory observation, in-depth interviews, and documentation. The results showed that PAI teachers play an important role in shaping students' character through their roles as teachers, mentors, and role models. The character of faith is formed through the habituation of prayer and surah memorisation; the character of piety is developed through the understanding of Qur'anic values associated with social practices; while the character of noble character is instilled through exemplary in daily attitudes and behaviour. The findings confirm the importance of integrating Islamic values in the learning process and strengthening character in the school environment. The contribution of this research lies in strengthening the contextual perspective in Islamic-based character education that is in line with the implementation of Merdeka Curriculum in pesantren-based education units